The Ulama Perspective toward The Status of Qirâat Sab’ah - Syar'i Sumin (AHKAM : Jurnal Ilmu Syariah, 2015)
This article is a preliminary attempt do discuss and trace the status of qirâat sab’ah from the perspective of ulama. The writing of this article is done based on library research. The data, concept and theory for this writing are taken from ideas, concepts and theories written by ulama as stated in the list of references at the end of this article. The result of the analysis in this article indicates two main things related to the status of qirâat sab’ah, there are qirâat sab’ah is recognized as qirâat mutawâtir and as qirâat mutawâtir, it has fulfilled the criteria as proposed by well-known Islamic ulama.DOI: 10.15408/ajis.v15i1.2842